Seed germination and dormancy characteristics of a collection of rice genotypes of northern Kerala - Karthika, V. P.; Retheesh, P. K.; Kalladan, Rajesh; Vanaja, T. (Journal of Scientific Agriculture, 2025)
An experiment was conducted at the Regional Agricultural Research Station, Pilicode (12.20° N, 75.16° E) of Kerala Agricultural University, to study the germination and dormancy characteristics of 27 rice genotypes cultivated in northern Kerala. The study revealed the significant variation among the genotypes with respect to percentage and speed of germination. At two weeks after harvest, ‘Japan Violet’ and ‘Manuratna’ showed the highest percentage of germination whereas ‘Kavungin poothala’ and ‘Kandorkutti’ exhibited the highest dormancy. Out of the seven very strong genotypes identified, ‘Kavungin poothala’ could reach 80% germination at seventh month after harvest only. Irrespective of the presence of dormancy, higher mean speed of germination among genotypes was observed at two months after harvest and similar vigour was maintained up to seven months. Among the genotypes, ‘Manuratna’ exhibited good germination even after one year. ‘Jeeakashala’ and ‘Chettadi’ also retained viability and vigour till one year though both exhibited seed dormancy at two weeks after harvest.